THE IMPLEMENTATION OF PROBLEM POSING APPROACH TO IMPROVE THE MATHEMATICAL CREATIVE THINKING ABILITIES OF JUNIOR HIGH SCHOOL - Permana, Neda; Rohaeti, Euis Eti; Purwasih, Ratni (Universitas Negeri Makassar, 2019)
The purpose of this study was to determine the increase in creative thinking skills of junior high school students who use learning by using the problem posing approach and the scientific approach to classroom learning, especially in mathematics. Quasi experiment is this type of research with the control group pre test and post test design. The research was conducted at one of the junior high schools in Cimahi City. As many as 62 students of class VII being sampled in this study consisted of 30 students in the experimental class with problem posing learning and 32 students in the control class with scientific learning. The testing in this study uses IBM SPSS version 22 software. The conclusions from the results of this study are 1) Increasing the ability of mathematical creative thinking by using a problem posing approach better than the scientific approach, 2) A problem posing approach if it is well planned for effectiveness when learning takes place, and 3) Students who are inaccurate in solving the problem of the ability to think creatively because they do not understand the problems asked in the questions. This can be seen from several responses of students who are incomplete in giving responses